2020
DOI: 10.1097/md.0000000000022464
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and causes of visual impairment among ethnic Tujia adults in a rural community in China

Abstract: We aimed to investigate the prevalence and causes of visual impairment (VI) in an elderly Tujia ethnic rural population in Southwest China. From June 1 to December 31, 2018, a random cluster sampling survey was conducted among Tujia individuals aged 50 years or older in the rural areas of Qianjiang District County in Chongqing. The sampling design used village-based clusters of approximately equal size (1000 people). The sampling frame was composed of 110 clusters including 26,527 adults aged 50 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The current study revealed that the magnitude of VI among medicine and health science students was 12.5% (95% CI: 10.21, 15.31%), which is comparable with a study done on adults in China (15.2%) [ 33 ], and Saudi Arabia (13.9%) [ 34 ], (14.90%) [ 35 ], respectively. However, the finding of this study was higher than the prevalence reported in Ghana 5.8% [ 36 ], Nigeria (5.02%) [ 37 ], (3.5%) [ 38 ], USA (7.5%) [ 39 ], Malaysia (8.9%) [ 40 ] and china (2.7%) [ 41 ].…”
Section: Discussionsupporting
confidence: 85%
“…The current study revealed that the magnitude of VI among medicine and health science students was 12.5% (95% CI: 10.21, 15.31%), which is comparable with a study done on adults in China (15.2%) [ 33 ], and Saudi Arabia (13.9%) [ 34 ], (14.90%) [ 35 ], respectively. However, the finding of this study was higher than the prevalence reported in Ghana 5.8% [ 36 ], Nigeria (5.02%) [ 37 ], (3.5%) [ 38 ], USA (7.5%) [ 39 ], Malaysia (8.9%) [ 40 ] and china (2.7%) [ 41 ].…”
Section: Discussionsupporting
confidence: 85%
“…There is known variability in the etiologies included in the definition of VI; this heterogeneity can influence the incidence and prevalence rates. The leading causes of VI have been reported to be cataract, uncorrected refractive error and posterior segment disorders including age-related macular degeneration, myopic macular degeneration, diabetic retinopathy, and other optic nerve atrophy ( 16 , 18 ). Twenty-seven articles were reviewed in total; refractive error constituted a VI factor in 25 studies, cataract in 23 studies, posterior segment disorders in 17 studies and glaucoma in 9 studies, respectively.…”
Section: Visual Impairment In Mainland Chinamentioning
confidence: 99%